2020
DOI: 10.1364/oe.386438
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of Y-doped VOx microbolometers with nanomesh antireflection layer

Abstract: In the study, the yttrium (Y)-doped vanadium oxide (VOx:Y) films used as the sensitive layers of microbolometers were deposited using a radio frequency magnetron co-sputtering system. The temperature coefficient of resistance (TCR) of the VOx:Y films was enhanced from −1.88%/°C to −2.85%/°C in comparison with that of the VOx films. To further improve the performance of microbolometers, the nanomesh antireflection layer was placed on the top surface of the microbolometers to reduce the infrared reflection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The D* value of visible to NIR wavelengths is greater than 1.79 × 10 9 Jones, both in air and under vacuum. Especially under vacuum, the D* value under 1550 nm is 6.02 × 10 9 Jones, which is higher than 6 × 10 8 Jones for a α-Si type bolometer and 2.20 × 10 8 Jones for a reported VO x type bolometer …”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The D* value of visible to NIR wavelengths is greater than 1.79 × 10 9 Jones, both in air and under vacuum. Especially under vacuum, the D* value under 1550 nm is 6.02 × 10 9 Jones, which is higher than 6 × 10 8 Jones for a α-Si type bolometer and 2.20 × 10 8 Jones for a reported VO x type bolometer …”
Section: Resultsmentioning
confidence: 72%
“…On the whole, in comparison with the novel bolometer materials in Table S1, VO 2 (B) shows superior TCR and a low noise level, leading to a significantly enhanced D* value. It is not only superior to existing bolometers , but also comparable to the state of the art ultra-broad-band photodetectors from the visible to the terahertz region (Table ). Our result shows the 2D metallic metal oxide is competitive in ultra-broad-band photodetection.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies on -based bolometers have reported TCR values of −3.5% [ 32 ], −2.3% C [ 33 ], −1.88 to −2.85% C [ 34 ] and −2.9% [ 35 ]. The TCR values reported in this work (about −3.9% ) are higher than the reported values and this is most likely associated with the higher resistivity of the films under study in this work.…”
Section: Resultsmentioning
confidence: 99%
“…As was already mentioned, such films are widespread and usually used for the fabrication of various pyro-and piezoelectric sensors. Both types of detectors have approximately the same sensitivity to heating on the order of 10 8 cm √ HzW −1 [31,32]. We gave preference to the second option, as it allows the use of an individual sensor for each new sample due to its low cost and ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%